ISOLATION, PURIFICATION AND CHARACTERIZATION OF EXTRACELLULAR MYCOTOXIN FROM Alternaria alternata (Basrah Journal of Veterinary Research)
The isolate of Alternaria alternata that isolated from soil produced extracellularsecondary metabolites (Mycotoxin) of carbohydrate with reducing nature which hadinhibitory effect against Gm positive & Gm negative standard and pathogenic bacteria insolid media. Three types of media Malt Extract Agar (MEA), Potato Dextrose Agar(PDA) and Potato Carrot Agar (PCA) can be using as solid or liquid media for productionthis mycotoxin. The mycotoxin extracted from free cell supernatant by simple extractionmethod using ethanol 90%. The cytotoxicity of extracted mycotoxin against human bloodcells (RBCs) was (25) ppm. The acute toxicity of extracted toxin as determined by LD50of laboratory mice was 150 mg/kg.